Effect of Quetiapine on Per1, Per2, and Bmal1 Clock Gene Expression in the Mouse Amygdala and Hippocampus - Shunpei Moriya; Yu Tahara; Hiroyuki Sasaki; Yutaro Hamaguchi; Daisuke Kuriki; Ryosuke Ishikawa; Jun Ishigooka; Shigenobu Shibata (Elsevier, 2014)
Abstract.: Circadian rhythms are related to various psychiatric disorders. Recently, antipsychotics, including quetiapine (QTP), have been accepted as potential therapeutic agents for the treatment of depression, but its mechanism remains poorly understood. In this study, we examined clock gene fluctuation patterns in QTP-treated mice. QTP significantly increased Per2 mRNA at ZT12 and Per1 and Per2 expression at ZT18 in the amygdala. There were significant differences between the control and QTP groups in the cross-time effects of Per2 mRNA expression in the amygdala. Our findings suggest that QTP possibly acts on the circadian system, which then induces changes in mood symptoms. Keywords:: quetiapine, clock gene, depression